2020
DOI: 10.1159/000511971
|View full text |Cite
|
Sign up to set email alerts
|

Wiedemann-Steiner Syndrome as a Differential Diagnosis of Cornelia de Lange Syndrome Using Targeted Next-Generation Sequencing: A Case Report

Abstract: Wiedemann-Steiner syndrome (WDSTS) is a rare autosomal dominant disorder with a variable clinical phenotype including synophrys, hypertelorism, thick eyebrows, long eyelashes, wide nasal bridge, long philtrum, hypertrichosis, growth retardation, and intellectual disability. Cornelia de Lange syndrome (CdLS) is a rare disease characterized by synophrys, long eyelashes, limb abnormalities, generalized hirsutism, growth retardation, and intellectual disability. In both WDSTS and CdLS, the malformations are due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…However, the combination of ptosis and long eyelashes was more frequent in KMT2A patients than NIPBL patients (24). Four of these six patients (two patients in our study and two patients in literature) had features of ptosis and hypertelorism, which may help to distinguish WDSTS and CdLS (13,16).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, the combination of ptosis and long eyelashes was more frequent in KMT2A patients than NIPBL patients (24). Four of these six patients (two patients in our study and two patients in literature) had features of ptosis and hypertelorism, which may help to distinguish WDSTS and CdLS (13,16).…”
Section: Discussionmentioning
confidence: 51%
“…In this study, we analyzed six patients with features of CdLS, and identified six variants in five non-cohesion genes. To date, 40 sporadic patients with features of CdLS caused by non-cohesion variants had been reported (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). We also evaluated the clinical features of these patients, and calculate the clinical scores of these patients according to the 2018 consensus statement to assess the reliability of 11-points scale criteria in the diagnosis of CdLS.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, cryptorchidism, not reported in patients with SBDS mutations (PubMed and Google Scholar search, June 2022, using cryptorchidism AND Shwachman-Diamond Syndrome), is present in UPN 43, its prevalence in the normal population is 1.7%, and observed in about 20–35% of WDSTS cases [ 49 , 61 , 62 ]. However, despite the fact that cryptorchidism has been reported in some WDSTS patients, it has never been associated with KMT2A mutations; instead, it has been associated with TASP1, which is a regulator of KMT2A [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, CdLS is now considered a “clinical spectrum” rather than an isolated syndrome with unique features ( Selicorni et al, 2021 ). Genes found mutated in patients with an initial diagnosis of CdLS are: EP300 (( Aoi et al, 2019 ) - Patient 6; ( Cucco et al, 2020 ); - Patient A; ( Squeo et al, 2020 ); - GDB1418; ( Woods et al, 2014 ); - Case Report)), KMT2A (( Yuan et al, 2015 ) - CdLS-3 (BAB4964); ( Parenti et al, 2017 ); - Patient 12; ( Aoi et al, 2019 ); - Patient 27; ( Demir et al, 2021 ); - Case Report)); TAF1 (( O’Rawe et al, 2015 ) - Individual 4A; ( Cheng et al, 2020 ); - Individual 13) causative of Mental Retardation X-Linked Syndromic 33 (MRXS33, OMIM # 300966 )); ZMYND11(( Aoi et al, 2019 ) - Patient 53) causative of Mental Retardation Autosomal Dominant 30 (MRD30, OMIM # 616083 )); PHIP (( Aoi et al, 2019 ) - Patient 56) associated to Developmental Delay Intellectual Disability Obesity and Dysmorphism or Chung-Jansen syndrome (CHUJANS, OMIM # 617991 )), CREBBP (( Tang et al, 2019 ) - Patient 3)); SETD5 (( Squeo et al, 2020 ) - GDB1400) causative of MRD23). These genes, involved in chromatin regulation, are associated with syndromes different from CdLS, but studies conducted exploiting animal models highlighted some similar characteristics that can be found in the human patients affected with CdLS.…”
Section: Animal Models For Chromatinopathiesmentioning
confidence: 99%